2016
DOI: 10.4103/0972-4052.176533
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of adding a supporting implant in stress distribution of long span fixed partial denture (three-dimensional finite element analysis)

Abstract: Context and Aims:Long span is seen in many clinical situations; treatment planning options of these cases are difficult and may require: Fixed partial denture (FPD), removable partial denture, or implant supported prostheses. Each option has its own disadvantages: Mechanical, patient relief, and cost, respectively. This article will evaluate the stress distribution of another treatment option, which is adding a single supporting implant to the FPD using three-dimensional (3D) finite element analysis.Subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…[ 17 ] Cone beam computed tomography-guided implant placement in the anterior maxilla will overcome the possibility of an angulated abutments, yet expensive; hence, its use can be restricted to place multiple implants in the same region. [ 35 36 37 38 ] Therefore, further studies can be carried out with improvements made to finite element models with respect to geometry of implants with regard to thread pitch, thread shape, and thread depth, applying dynamic loading conditions depending on the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Cone beam computed tomography-guided implant placement in the anterior maxilla will overcome the possibility of an angulated abutments, yet expensive; hence, its use can be restricted to place multiple implants in the same region. [ 35 36 37 38 ] Therefore, further studies can be carried out with improvements made to finite element models with respect to geometry of implants with regard to thread pitch, thread shape, and thread depth, applying dynamic loading conditions depending on the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mozayek et al [9], discussed the effectiveness of adding a supporting implant in stress distribution of long-span fixed partial dentures using three-dimensional finite element analysis. The study concluded that adding a supporting implant has no mechanical advantages, whereas it has the disadvantages of complicating treatment and the complications that may occur to the implant and surrounding bone itself.…”
Section: Introductionmentioning
confidence: 99%